The Effect of Workload and Work Stress on Employee Performance with Motivation as an Intervening Variable: The Case at Bhayangkara Hospital, Palembang - Devi Sukadiah; Diah Isnaini Asiati; Choiriyah Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The purpose of this study is to determine the effects of organizational culture, work motivation, and organizational commitment on employee performance in the Coal Handling and Transportation Unit of PT. Bukitasam, Tbk, Tanjung Enim Mining Unit. This study is a causal associative study using a quantitative approach. The population used in this study comprised all employees of the Coal Handling and Transportation Division of PTBA UPTE, totaling 152. The sample used a purposive sampling technique with a Slovin formula of 111 respondents. The study's results indicate that organizational culture, motivation, and organizational commitment influence employee performance in the Coal Handling and Transportation Unit of PT. Bukit Asam Tbk, Tanjung Enim Mining Unit, both partially and simultaneously.